That time I got reincarnated as a slime. 11 - Fuse (Manga author); Kawakami, Taiki (Kodansha Comics, 2019)
"As players of Monster Hunter and Dungeons & Dragons know, the slime is not exactly the king of the fantasy monsters. So when a 37-year-old Tokyo salaryman dies and wakes up in a world of elves and magic, he's a little disappointed to find he's become a blind, boneless slime monster... Rimuru's taking a break from managing his kingdom of monsters by honoring the memory of his friend Shizu. Her former pupils will perish if he can't find a way to rein in their unstable magical energy and he might just have the answer. It will involve enlisting the help of powerful elemental spirits--but he's about to find out that their fairy queen is a bit of a loose cannon..."--Provided by publisher.